BHŪTA KŌLA RITUAL SPIRIT POSSESION IN MANGALORE: THROUGH THE SPECTACLES OF IDENTITY POLITICS - Monteiro, Thomas; Sakshi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In modern times politicization, popularization and commercialization of Bhūta Kōla, is with a particular purpose. As it is said today politics is played by mass mobilization of the people. The best way to mobilize the people is through identity. Appealing to the identity of the people is done through folk stories, myths, or any other social identities (race, religion, caste). Identity Politics is played in either way, it can be used by the dominant group to legitimize the existing social and political structures by legitimizing the anti-structural resistance performed through certain rituals and celebrations like that of Bhūta Kōla. It helps them to neutralize and further legitimize the silent background consensus. In this way the dominant group makes use of identity politics only to legitimize the power not for the real concern for transformation. On the other hand the dominated (marginalized) group too makes use of Identity Politics to question the existing relations of power.